2012
DOI: 10.1038/nm.2999
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-triggered cathepsin B release in myeloid-derived suppressor cells activates the Nlrp3 inflammasome and promotes tumor growth

Abstract: Chemotherapeutic agents are widely used for cancer treatment. In addition to their direct cytotoxic effects, these agents harness the host's immune system, which contributes to their antitumor activity. Here we show that two clinically used chemotherapeutic agents, gemcitabine (Gem) and 5-fluorouracil (5FU), activate the NOD-like receptor family, pyrin domain containing-3 protein (Nlrp3)-dependent caspase-1 activation complex (termed the inflammasome) in myeloid-derived suppressor cells (MDSCs), leading to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
514
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 636 publications
(540 citation statements)
references
References 45 publications
13
514
1
2
Order By: Relevance
“…64,65 Recently, gemcitabine and 5-FU were shown to activate the inflammasome pathway in MDSCs, leading to IL-1b production, which, in turn, induced IL-17 secretion by CD4 T-cells and blunted the anticancer efficacy of chemotherapy. 66 In another report, however, optimal anticancer responses during doxorubicin treatment have been shown to require the IL-17-producing gd T-cell population. 52 A dosedependent effect on the expansion or differentiation of CD4 Tcells producing IL-17A was also observed in naive and tumorbearing mice following treatment with CTX.…”
Section: Box 1 Immune-based Effects Of Targeted Anticancer Compoundsmentioning
confidence: 99%
“…64,65 Recently, gemcitabine and 5-FU were shown to activate the inflammasome pathway in MDSCs, leading to IL-1b production, which, in turn, induced IL-17 secretion by CD4 T-cells and blunted the anticancer efficacy of chemotherapy. 66 In another report, however, optimal anticancer responses during doxorubicin treatment have been shown to require the IL-17-producing gd T-cell population. 52 A dosedependent effect on the expansion or differentiation of CD4 Tcells producing IL-17A was also observed in naive and tumorbearing mice following treatment with CTX.…”
Section: Box 1 Immune-based Effects Of Targeted Anticancer Compoundsmentioning
confidence: 99%
“…In mice, 5-FU induces caspase-1 activation and IL-1β release and induces the generation Th17 cells, which is inhibited by anakinra. 9 We observed a significant activation of caspase-1 in monocytic Myeloid derived suppressor cells (mMDSC) and a significant increase of serum IL-1β…”
Section: Resultsmentioning
confidence: 85%
“…Indeed, Caspase-1 activation and IL-1β release has been observed 24 hours after the first 5-FU injection. We previously observed that 5-FU regimen or FOLFOX regimen 9,17 prompts the accumulation of Th17 in patients’ blood and reduces the number of mMDSC. Immunomonitoring underlines a decrease in the number of mMDSC and the inversion of granulocyte/lymphocyte ratio after therapy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations